Beyond the simple contrastive analysis: Appropriate experimental approaches for unraveling the neural basis of conscious experience - Talis Bachmann (Frontiers Research Topics, 2015)
Contrasting conditions with and without conscious experience has served consciousness research well. However, research based on this simple contrast has led to controversies about the neural basis of conscious experience. One key reason for these ongoing debates seems to be that the simple contrast between conditions with and without consciousness is not specific for unraveling the neural basis of conscious experience, but rather also leads to other processes that precede or follow it. Acknowledging this methodological problem implies that some of the previous research findings about the neural underpinnings of conscious experience are actually reflecting the prerequisites and consequences rather than the direct correlates of conscious perception. Thus, it is required to re-evaluate the previous results to find out which of them are telling us anything about the neural basis of consciousness. But first and foremost, to overcome this methodological problem we need new experimental paradigms that go beyond the simple contrastive analysis or find the ways how some older but well forgotten paradigms may foster a new look at this emerging problem. Accordingly, this research topic is looking for empirical and theoretical contributions that: 1) envision new and suitable experimental approaches to study consciousness that are free from the limitations of the simple contrastive analysis; 2) provide empirical data that help to separate the neural correlates of conscious experience from the prerequisites and consequences of it; 3) help to re-assess previous research findings about the neural correlates of conscious perception in the light of the methodological problems with the traditional contrastive analysis. We hope that the theoretical insights and experimental approaches collected within this Research Topic help us to gain a more refined understanding of the neural basis of conscious experience.